Іоанн Максимович: соціальні аспекти творчості (1651 – 1715) - Половець, В. (Сiверянський лiтопис, 2016)
Запропонована увазі читачів стаття має на меті ознайомити з постаттю Іоанна
Максимовича та розкрити роль його творчості в духовно-соціальному розвитку суспільних відносин, показати святителя як невтомного трудівника на літературній ниві. Предложенная вниманию читателей статья имеет целью познакомить с личностью Иоанна Максимовича и раскрыть роль его творчества в духовно-социальном
развитии общественных отношений, показать святителя как неутомимого труженика на литературной ниве. Ioann Maksimovich was born in the second half of the XVII century. In the conditions of
modern times when important contribution to the development of social relations was made
by the representatives of the era of humanism he defended the clergy and called by «the
power of the church» to «obedience» and to the whole domination of Christian theology.
According to the Holy, Monotheistic Christianity was fully complied with monarchy. However
of the reason of the triumph of Christianity there was a decline of ancient culture. The new
religion became a dominant element of the spiritual life of society and conquered all cells
of the social organism. Since scholastic theology dominated over the scientific knowledge
which were under the patronage of Christian theology. The most famous treatises of church
ideologues of those times were dedicated to theological issues. All social phenomena were
considered in the context of Christian philosophy from that time, and person was thought of
as a God’s creation product. The essence of wisdom was in the intention of comprehension
God and science had to facilitate this process.
Analysis of Ioann Maksimovich works shows that the author was a broadly educated man
and he had a great experience in working with people. He had a wide knowledges of Holy
Scripture, of God,s creation, also he knew history, Greek and Roman antiquities and pagan
mythology very well. He was a tireless worker in the literary field, enriched the clergy and
their congregation by instructive works. According to his patron Ioann Zlatoust he had the rare
gift of word and this gift was clearly reflected in all his works. The works of the Holy made
a significant contribution to the theory of theological and church sermons and unsurpassed
impact on social relations in society.